Three-dimensional echocardiography in congenital heart disease. - Li, J; Sanders, S P (Current Opinion in Cardiology, 1999)
Recent advances in transducer technology and image processing have led to the development of two techniques for three-dimensional (3-D) echocardiography: 1) 3-D reconstruction and 2) real-time 3-D (RT3-D) volumetric imaging. 3-D reconstruction creates a 3-D data set from a series of two-dimensional (2-D) images. RT3-D echocardiography uses a 2-D matrix phased array transducer with multiple parallel processing to produce real-time volumetric images of the heart. Both technologies produce novel views of congenital heart defects and offer improved quantification of ventricular volume, mass, and function. The main advantage of RT3-D imaging is its ability to capture 3-D data in real time. This avoids the motion artifact inherent with any reconstructive technique and permits analysis of events during a single cardiac cycle; however, at present, RT3-D imaging has poorer image quality and lacks the Doppler capability. Further development in both techniques will allow 3-D echocardiography to have more widespread clinical applicability.